Jokowi’s Food Sovereignty Narrative: Military in the Rice Land? - Lassa, Jonatan Anderias (2015)
The Jokowi cabinet is planning to involve the country’s military in agriculture and food security affairs in order to achieve food sovereignty and 100 percent rice self-sufficiency. What would be the implications for the country’s long term food security?